Analisis kandungan terhadap penampilan kandungan, soalan dan aktiviti buku teks Bahasa Melayu Kurikulum standard Sekolah Rendah Tahap Dua: Data Anekdot - Habibah @ Artini Ramlie; Norshahrul Marzuki Mohd. Nor; Zaharah Hussin (Universiti Putra Malaysia, 2020)
This qualitative study aimed to examine the appearance of Bahasa Melayu Primary School Standard Curriculum (KSSR) textbooks level two. Researchers use anecdotal data analysis as a techniqueof data collection and its analysis. The focus of the study was onthe appearance of the contents of the textbook, the instructions and content of the activities and the questions displayed. The data were qualitatively collected based on anecdotal data analysis form adapted by researcher from previous studies. The findings show that the appearance of the contents of Bahasa Melayu textbooks KSSR quite interesting in terms of visual display and has good continuity and sequence of topics and sub-topics. However, some activities and exercises showed certain weaknesses such asinstructions that are relatively general and unclear, repetitive and less likely to lead to critical thinking, problem solving and analogy.